2003
DOI: 10.2320/matertrans.44.476
|View full text |Cite
|
Sign up to set email alerts
|

Microstructures and Tensile Properties of ECAE-Processed and Forged AZ31 Magnesium Alloy

Abstract: In order to achieve same level of high strength and high ductility as 6061 aluminum forging alloy that is currently used for automobile applications, AZ31 magnesium alloy rod with a large diameter of 40 mm was subjected to ECAE-processing, and the microstructures and mechanical properties of the ECAE-processed specimens were investigated. Furthermore, automobile knuckle arm was produced by forging using the ECAE-processed material, and the mechanical properties of the forged product and their strain rate depen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
16
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(18 citation statements)
references
References 18 publications
2
16
0
Order By: Relevance
“…Due to the fact that it is likely that buckling and cracks will occur, the design is carried out in two forging stages: preform and final cam. Cisar et al [22] manufacture a knuckle arm, which forms part of the steering system of an automobile, from ECAP-processed AZ31 magnesium alloy. AZ31 is subjected to up to four ECAP passages at a temperature of 250 °C and then, it is forged at a temperature of 150 °C.…”
Section: Optimization Of the Die Design For Manufacturing The Camsmentioning
confidence: 99%
See 1 more Smart Citation
“…Due to the fact that it is likely that buckling and cracks will occur, the design is carried out in two forging stages: preform and final cam. Cisar et al [22] manufacture a knuckle arm, which forms part of the steering system of an automobile, from ECAP-processed AZ31 magnesium alloy. AZ31 is subjected to up to four ECAP passages at a temperature of 250 °C and then, it is forged at a temperature of 150 °C.…”
Section: Optimization Of the Die Design For Manufacturing The Camsmentioning
confidence: 99%
“…From ECAP-processed AA6061 (twelve times using route Bc), Kim et al [12] manufacture a micro-gear by extrusion at temperature values of 443 K and 553 K. One of their most remarkable conclusions is that the extrusion process may be carried Cisar et al [22] manufacture a knuckle arm, which forms part of the steering system of an automobile, from ECAP-processed AZ31 magnesium alloy. AZ31 is subjected to up to four ECAP passages at a temperature of 250 • C and then, it is forged at a temperature of 150 • C. One of the aims of this research work is to evaluate the applicability of ECAP-processed materials to the manufacturing of industrial components.…”
Section: Introductionmentioning
confidence: 99%
“…It has been demonstrated that the ECAE process can produce materials with a sub-micro crystalline structure, [9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24] including magnesium alloys. [18][19][20][21][22][23] Very recently, Cisar et al 25) performed hot forging using ECAE-processed AZ31 alloy at 573 K. They succeeded in fabricating an automobile knuckle arm. However, the forming characteristics have not been analyzed.…”
Section: Introductionmentioning
confidence: 99%
“…To form various parts of magnesium alloys, methods to fabricate plate-or sheet-form parts with ribs and/or bosses need to be developed, and forging is one of the promising methods to accomplish this. [2][3][4][5][6][7][8] The authors have already successfully fabricated plate-form parts with a boss in magnesium alloys by superplastic forging. 9,10) One of the principal types of defect in closed-die forging is extrusion-type defects, 11) which are formed when centrally located ribs and bosses, formed by extrusion-type flow, draw too much metal from the main body of the forging.…”
Section: Introductionmentioning
confidence: 99%